Wnt Inhibitors and Bone Turnover Markers in Patients With Polymyalgia Rheumatica and Acute Effects of Glucocorticoid Treatment - Fassio, Angelo; Adami, Giovanni; Idolazzi, Luca; Giollo, Alessandro; Viapiana, Ombretta; Vantaggiato, Elisabetta; Benini, Camilla; Rossini, Maurizio; Dejaco, Christian; Gatti, Davide (Frontiers in Medicine, 2020)
Background In polymyalgia rheumatica (PMR), data on bone turnover markers (BTM), on Wnt inhibitors (Dkk-1, sclerostin) and their changes induced by glucocorticoids (GC) are lacking. The aims of our study were to compare the baseline levels of Wnt inhibitors and BTM in PMR patients with healthy controls (HC) and to study their changes over the first 4 weeks of GC treatment. Materials and methods We enrolled 17 treatment-naïve patients affected by PMR and 17 age and sex-matched healthy controls (HC) from retired hospital personnel. PMR patients were administered methylprednisolone 16 mg daily for 4 weeks. Blood samples were taken at baseline and at week 4 for the PMR group, a single sample was taken for HC. N-propeptide of type I collagen (PINP), C-terminal telopeptide of type I collagen (CTX-I), sclerostin, Dkk-1 and C-reactive protein (CRP) were dosed. Results At baseline, Dkk-1 was significantly higher in the PMR group as compared to HC (p=0.002) while PINP, CTX-I and sclerostin levels were comparable between PMR patients and HC., After 4 weeks of GC treatment we found in the PMR group a decrease of PINP (mean ± SD percentage decrement as compared to baseline -40±18.6%, p<0.001), CTX-I (-23.5±41.3%, p=0.032), Dkk-1 (-22.4±39.6, p = 0.033) and sclerostin (-32.49±20.47, p<0.001) as compared to baseline levels. Conclusions In treatment-naïve PMR, systemic inflammation is associated with a dysregulation of the Wnt system (increased Dkk-1). Within the first month, treatment with GC showed noteworthy effects on bone resorption, formation and on Wnt pathway modulators.